De escravos a cidadãos os caminhos das políticas públicas para as comunidades remanescentes de quilombos na Paraíba - Negócio, Carla Daniela Leite (2016)
The present research deals with the dominance of Western knowledge and its modes of production and appropriation of natural resources, overlapping with other forms of knowledge that could lead to a more harmonious relationship with the environment. It analyzes the artifice that this Western knowledge used to overcome the alternative ways of thought, disqualifying them and leading them to non-existence. It also leads to the discussion of the Human Rights and, in particular, of public policies, seen in this research as an instrument for the realization of these rights. In this context, we try to understand the role that the development model plays in our society and its impacts, especially on so-called minority groups. It also demonstrates that public policies are a valuable instrument for the realization of human rights and the construction of equality, being a valuable instrument available to the Government and society to materialize and provide material efficacy to its precepts. It also analyzes public policies aimed at groups considered as traditional populations, especially the remnant communities of quilombos. Public policies aimed at these groups and their implementation are studied, as well as the importance of their effective participation in all stages of these policies. It is concluded, at the end, that there have been great advances in these areas, but in order to have an effectively transforming policy it is necessary to have the effective inclusion of those interested in the projects to which they are addressed.